PENGARUH KEPEMILIKAN SAHAM, KEBIJAKAN DIVIDEN, TANGIBILITY, SIZE, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL - Laksana, Intan Frintia; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Capital structure is an important issue for the company. Good or bad of the capital structure has direct effect to the financial position of the company. In order to deal with this problem, a company should find some alternatives of the selected fund sources. Financial manager should determine the optimal capital structure i.e. the combination of debt and equity which can maximize the firm value. The purpose of this research is to test the influence of stock ownership (managerial ownership and institutional ownership) dividend policy, tangibility (assets structure) firm size and profitability to the capital structure. The sample collection technique has been done by using purposive sampling method, and based on the determined criteria, 45 companies have been selected as samples. This research applies classic assumption test and multiple linear regressions analysis test which has been done by using statistic test of SPSS 20 version. The result of this research shows that institutional ownership, tangibility (assets structure) and firm size have positive influence to the capital structure. The dividend policy and profitability has negative influence to the capital structure. Meanwhile, managerial institution does not have any influence to the capital structure.Keywords: Stock Ownership, Dividend Policy, Tangibility (Assets Structure), Profitability, Capital Structure.